Tactical-technical actions and internal load of young futsal players: role of space and player numbers - Adriano Gomes, S.; Travassos, B.; Nuno Ribeiro, J.; Asín-Izquierdo, I.; Castro, H. de O.; Lume Gomes, L.; Ernesto Santos Ferreira, C. (International Journal of Performance Analysis in Sport, 2025)
This cross-sectional study aimed to analyse the effects of manipulating game space and number of players on the tactical-technical actions and internal load (IL) of young futsal players. Forty-two male Under-17 (U-17) players (age = 15.62 ± 0.58 years) from three futsal teams participated. The tasks analysed were GK + 2 × 2+GK and GK + 3 × 3+GK in 20 × 20(T1/T4), 30 × 20(T2/T5) and 40 × 20(T3/T6) and GK + 4 × 4+GK in 40 × 20meters (T7). The tactical-technical performance analysis was performed using Videobserver® software. The IL demands during futsal tasks was performed using the RPE and RPE-session (s-RPE). The results showed how passing, RPE and s-RPE increased in tasks where the relative surface area per player was higher than that of the competition (>80 m2), both in relation to larger spaces and with fewer players (mainly, T2, T3 and T6). Shooting actions increased in tasks with smaller space and fewer players (T1/T4). Total offensive actions increased when the number of players was reduced, tending to increase with greater playing space (mainly, T2 and T3). In general, the competition format represented the lowest values (T7). Manipulating futsal tasks allows coaches to adjust them to training and competition objectives. These results represent an advance in futsal research, requiring future studies.